The Impact of the Consumption of Hazardous Chemicals on the Development of Agritourism in Serbia - Matijašević Obradović, Jelena D; Lukavac, Jelena Z; Miletić, Ljiljana Z; Ničić, Milica S; Mitrović, Nenad Lj (Industrija, 2017)
The primary attention in considering the fact that the percentage of hazardous chemicals consumption is inversely proportionate to the quality of ecological potential as one of the basic principles of rural development, which has direct implications for the development of agritourism, the research into the consumption of hazardous chemicals covering the period from 2011 to 2015 in the Republic of Serbia in comparison to EU 28 was conducted. The research was focused on the consumption of hazardous chemicals by divisions of Classification of activities, the consumption of hazardous chemicals by toxicity classes (A-E), and the analysis of the hazardous chemicals consumption by regions in the Republic of Serbia. The results obtained reveal the consumption of all hazardous chemicals classes per capita in Serbia is significantly lower than in the EU, and that the share of the most toxic classes is lower. Additionally, the trend of hazardous chemicals consumption is decreasing in Serbia, and stagnates in the EU. Particularly low consumption is registered in Southern and Eastern region as well as Sumadia and Western region, pointing out at the potential of these regions for development of agritourism based on this fact.
Keywords: Region; Consumption; Chemical